PENGENALAN PENYAKIT MENULAR SEKSUAL HUMAN IMMUNODEFICIENCY VIRUS-ACQUIRED IMMUNODEFICIENCY SYNDROME DI BUNDA MULIA SCHOOL JAKARTA - Dwiana, Alya; Ernawati, Ernawati; KD, Andriana (Jurnal Bakti Masyarakat Indonesia, 2020)
The trend of the prevalence of cases of sexually transmitted diseases (STDs) of Human Immunodeficiency Virus-Acquired Immunodeficiency Syndrome (HIV-AIDS) in the population aged 15-49 years increased from 0.16% to 0.43% in 2013 and will continue to increase. Many doctors and scientists have stated how important comprehensive prevention efforts are, before the prevalence of HIV STDs in the Asia-Pacific region increased to 10 million sufferers by 2020. Several factors influence the occurrence of HIV-AIDS STDs among adolescents, one of which is the lack of accurate information. Therefore, health education, especially sexual education and healthy living behaviors are teachings that can help adolescents to deal with life problems that originate from sexual drive and relationships. Education about how HIV-AIDS STDs are transmitted and prevented is the main weapon against HIV-AIDS STDs, because there is no treatment or vaccine that can prevent the spread of HIV-AIDS STDs. Counseling about STD HIV-AIDS is carried out at Bunda Mulia School, which is one of the youth communities that can be used as an example of efforts to prevent STD HIV-AIDS early. Prevention is carried out by interactive counseling in the form of discussions and question and answer sessions, which aim to provide a clear understanding for teenage students as well as teachers and school staff on how to prevent transmission of HIV-AIDS STDs. Before and after counseling, pre-test and post-test are held to assess whether there is a change in understanding of STD HIV-AIDS. The activity was followed by 88 students from grade 10-12. Overall, there was an increase in the knowledge of participating students about STD HIV-AIDS with an average point of 1.34 to 1.55 after participating in counseling activities. So it can be concluded that the objectives of extension activities have been achieved. ABSTRAK: Kecenderungan prevalensi kasus Penyakit Menular Seksual (PMS) Human Immunodeficiency Virus-Acquired Immunodeficiency Syndrome (HIV-AIDS) pada penduduk usia 15-49 tahun meningkat dari 0.16% menjadi 0.43% di tahun 2013 dan akan terus semakin meningkat. Banyak dokter dan ilmuwan telah menyatakan betapa pentingnya upaya pencegahan yang menyeluruh, sebelum prevalensi PMS HIV di wilayah Asia pasifik meningkat menjadi 10 juta penderita pada tahun 2020.Beberapa faktor yang mempengaruhi terjadinya PMS HIV-AIDS di kalangan remaja salah satunya adalah kurangnya informasi yang akurat. Maka dari itu, pendidikan kesehatan terutama pendidikan seksual dan perilaku hidup sehat merupakan pengajaran yang dapat menolong remaja untuk menghadapi masalah hidup yang bersumber dari dorongan seksual dan pergaulan. Pendidikan tentang bagaimana PMS HIV-AIDS ditularkan dan dicegah adalah senjata utama melawan PMS HIV-AIDS, karena tidak ada pengobatan atau vaksin yang dapat mencegah penyebaran PMS HIV-AIDS. Penyuluhan mengenai PMS HIV-AIDS dilakukan di Sekolah Bunda Mulia yang merupakan salah satu komunitas remaja yang dapat dijadikan sebagai contoh upaya pencegahan PMS HIV-AIDS secara dini. Pencegahan dilakukan dengan penyuluhan yang interaktif berupa diskusi dan sesi tanya jawab, yang bertujuan untuk memberikan pemahaman yang jelas bagi para siswa remaja serta guru dan petugas sekolah mengenai cara mencegah penularan PMS HIV-AIDS. Sebelum dan sesudah penyuluhan, diadakan pre-test dan post-test untuk menilai apakah ada perubahan dalam pemahaman mengenai PMS HIV-AIDS. Kegiatan diikuti oleh 88 siswa/i kelas 10-12. Secara keseluruhan terjadi peningkatan pengetahuan siswa peserta mengenai PMS HIV-AIDS dengan rata-rata poin 1.34 menjadi 1.55 setelah mengikuti kegiatan penyuluhan. Sehingga dapat disimpulkan bahwa tujuan kegiatan penyuluhan telah tercapai